2012
DOI: 10.1021/ef3009794
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Intake of Organic Shales

Abstract: Organic shales are exposed to treatment fluids during and after hydraulic fracturing operations. The fluid–shale interaction influences the petrophysical alteration of the fractured shale and the fate of the fracturing fluid. We systematically measured the spontaneous water and oil intake of five shale samples collected from the cores of two wells drilled in the Horn River basin. The samples represent three shale formations with different mineralogy and petrophysical properties. We characterize the samples by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
130
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(134 citation statements)
references
References 30 publications
4
130
0
Order By: Relevance
“…Fig. 1 illustrates the well as [10][11][12][13][14][15][16][17][18][19][20] hydrofractures that are H ∼ 30 m high and 2L ∼ 200 m long, spaced at distances of around 2d ∼ 100 m. The fact that this is the right starting point for these wells was recognized by Al-Ahmadi et al (9), and the diffusion problem in this setting has been studied by both Silin and Kneafsy (10), and Nobakht et al (11).…”
mentioning
confidence: 99%
“…Fig. 1 illustrates the well as [10][11][12][13][14][15][16][17][18][19][20] hydrofractures that are H ∼ 30 m high and 2L ∼ 200 m long, spaced at distances of around 2d ∼ 100 m. The fact that this is the right starting point for these wells was recognized by Al-Ahmadi et al (9), and the diffusion problem in this setting has been studied by both Silin and Kneafsy (10), and Nobakht et al (11).…”
mentioning
confidence: 99%
“…However, hydraulic fracturing triggers low recovery of fracturing fluids (usually <30% [4]), which raises concerns from both technical and environmental aspects. Several mechanisms have been proposed to understand why the fracturing fluids disappeared, e.g., remaining in fracture network [4,5], creating new fractures [6,7], hydration of clay minerals [8,9], capillary pressure [5][6][7]10], and osmotic flow [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The spontaneous imbibition is the dominant mechanism of the water transport into the formation because of the high capillary pressure by nanopores [17][18][19]. Recently studies have shown that the spontaneous imbibition of fracturing fluid can be a driving force to enhance the gas recovery for shale gas reservoir [20,21]. Thus, analysis of the spontaneous imbibition of shale and the potential effect on gas recovery needs urgent attention.…”
Section: Introductionmentioning
confidence: 99%